Gyejibongnyeong-Hwan (Gui Zhi Fu Ling Wan) Ameliorates Human Uterine Myomas via Apoptosis - Lee, So Min; Choi, Eun Som; Ha, Eunyoung; Ji, Kon Young; Shin, So Jin; Jung, Jeeyoun (Frontiers in Pharmacology, 2019)
Uterine leiomyomas are the most common benign neoplasms in women of reproductive age. However, non-surgical treatments for uterine myomas have not been fully evaluated. In Korea and China, Gyejibongnyeong-hwan (GBH) is widely used to treat gynecological diseases. Thus, we investigated the effects of GBH in human uterine myoma cells (hUtMCs). The hUtMCs were collected from patients undergoing curative surgery. Cell viability was analyzed via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. The expression levels of p53, Bax, Bcl-2, cleaved-caspase-3, and caspase-9 were determined by western blotting. Apoptosis and ROS levels were evaluated by fluorescence microscopy. First, we determined the adequate concentration that did not affect normal cells, and then investigated the time-dependent anti-neoplastic effect of GBH in order to decide the appropriate treatment time under a non-toxic concentration. Cell viability and number were significantly reduced by GBH at 48 h (P < 0.001) in a dose-dependent manner (0–200 µg/mL). The ratio of Bax to Bcl2, and expression of p53, cleaved-caspase-3 and caspase-9 increased, representing GBH induced apoptosis in uterine leiomyomas. In addition, treatment of pan-caspase inhibitor/p53 inhibitor with GBH rescued the GBH-mediated apoptotic effect. Furthermore, GBH significantly increased the mitochondrial ROS concentration, and mitochondria ROS scavenger reduced the percentages of early apoptosis cell. These results suggest that GBH may induced apoptosis of leiomyomas and demonstrated that GBH can be a potential therapeutic and/or preventive agent for uterine leiomyomas.